Hormonal drugs: Influence on growth, biofilm formation, and adherence of selected gut microbiota - Hammouda, Zainab K.; Wasfi, Reham; Abdeltawab, Nourtan F. (Frontiers in Cellular and Infection Microbiology, 2023)
Many studies have reported the influence of hormonal drugs on gut microbiota composition. However, the underlying mechanism of this interaction is still under study. Therefore, this study aimed to evaluate the possible in vitro changes in selected members of gut bacteria exposed to oral hormonal drugs used for years. Selected members of gut bacteria were Bifidobacterium longum, Limosilactobacillus reuteri, Bacteroides fragilis, and Escherichia coli representing the four main phyla in the gut. Selected hormonal drugs used for a long time were estradiol, progesterone, and thyroxine. The effect of intestinal concentrations of these drugs on the selected bacterial growth, biofilm formation, and adherence to Caco-2/HT-29 cell line was assessed. Short-chain fatty acids (SCFAs) have been included in host functions including the gut, immune and nervous functions; thus, the drug’s effects on their production were assayed using High- Performance Liquid Chromatography. Sex steroids significantly increased the growth of all tested bacteria except B. longum, similarly, thyroxine increased the growth of tested Gram-negative bacteria however reducing that of tested Gram-positive bacteria. The effect of drugs on biofilm formation and bacterial adherence to cell lines cocultures was variable. Progesterone decreased the biofilm formation of tested Gram-positive bacteria, it nevertheless increased L. reuteri adherence to Caco-2/HT-29 cell line cell lines coculture. By contrast, progesterone increased biofilm formation by Gram-negative bacteria and increased adherence of B. fragilis to the cell lines coculture. Moreover, thyroxine and estradiol exhibited antibiofilm activity against L. reuteri, while thyroxine increased the ability of E. coli to form a biofilm. Moreover, hormones affected bacterial adherence to cell lines independently of their effect on hydrophobicity suggesting other specific binding factors might contribute to this effect. Tested drugs affected SCFAs production variably, mostly independent of their effect on bacterial growth. In conclusion, our results showed that the microbiota signature associated with some hormonal drug consumption could be the result of the direct effect of these drugs on bacterial growth, and adherence to enterocytes besides the effect of these drugs on the host tissue targets. Additionally, these drugs affect the production of SCFAs which could contribute to some of the side effects of these drugs.